Circadian time-dependent effects of fencamfamine on inhibition of dopamine uptake and release in rat striatal slices - DeLucia, R.; Planeta, Cleopatra da Silva [UNESP]; Ferreira, M. P.; Aizenstein, M. L.; Scavone, C. (FapUNIFESP (SciELO), 1997)
Fencamfamine (FCF) is a central stimulant that facilitates central dopaminergic transmission through inhibition of dopamine uptake and enhanced release of the transmitter. We evaluated the changes in the inhibition of uptake and the release of striatal [ 3H]-dopamine at 9:00 and 21:00 h, times corresponding to maximal and minimal behavioral responses to FCF, respectively. Adult male Wistar rats (200-250 g) maintained on a 12-h light/12-h dark cycle (lights on at 7:00 h) were used. In the behavioral experiments the rats (N = 8 for each group) received FCF (3.5 mg/kg, ip) or saline at 9:00 or 21:00 h. Fifteen minutes after treatment the duration of activity (sniffing, rearing and locomotion) was recorded for 120 min. The basal motor activity was higher (28.6 ± 4.2 vs 8.4 ± 3.5 s) after saline administration at 21:00 h than at 9:00 h. FCF at a single dose significantly enhanced the basal motor activity (38.3 ± 4.5 vs 8.4 ± 3.5 s) and increased the duration of exploratory activity (38.3 ± 4.5 vs 32.1 ± 4.6 s) during the light, but not the dark phase. Two other groups of rats (N = 6 for each group) were decapitated at 9:00 and 21:00 h and striata were dissected for dopamine uptake and relase assays. The inhibition of uptake and release of [ 3H]-dopamine were higher at 9:00 than at 21:00 h, suggesting that uptake inhibition and the release properties of FCF undergo daily variation. These data suggest that the circadian time-dependent effects of FCF might be related to a higher susceptibility of dopamine presynaptic terminals to the action of FCF during the light phase which corresponds to the rats' resting period.
Keywords: behavior; chronopharmacology; dopamine release; dopamine uptake; fencamfamine; dopamine; fencamfamin; animal experiment; circadian rhythm; controlled study; corpus striatum; dopaminergic transmission; drug effect; intraperitoneal drug administration; nonhuman; presynaptic nerve; rat; Animals; Behavior, Animal; Central Nervous System Stimulants; Circadian Rhythm; Corpus Striatum; Dopamine; Dopamine Antagonists; Male; Norbornanes; Rats; Rats, Wistar; Animalia; Rattus norvegicus